Chromosphere Activity Relation with Solar Dynamo Magnetic Activity Cycle - Ehsan Tavabi; Mina Rajabi; Sima Zeighami (Iranian Journal of Astronomy and Astrophysics)
In this article, we analyzed the abnormal thickness of the chromosphere above the coronal holes (CH) at the poles of the Sun for 13 years (2010-2022), on the 15th of every month, by using AIA/SDO telescope data. We used the light emitted from helium-2 (He II) at a wavelength of 304 AA at about 50,000 K to investigate the solar holes in its north and south poles. This light is emitted from the chromosphere and the transition region. According to the values of the graphs obtained by the MATLAB program and the comparison between solar cycles during the 2010-2022 years, it was seen that the Full width of the intensity curves at half maximum (FWHM) in the poles, and as a result the magnetic activity of the sun and especially the activity of coronal cavities as the main source of the solar dipole magnetic field before cycle 25 is significantly greater than this thickness before cycle 24. According to the relationship between the number of sunspots and the solar activity in the coronal holes at the solar poles with a time delay of 2 to 5 years, we expect the maximum increasing in the number of sunspots around the year 2025. As a result,in terms of the number of sunspots, the height of the solar cycle 25 probably is higher than the cycle 24, which was a low sunspot number cycle. We also concluded that the thickness of the Chromosphere has an inverse relationship with solar dynamo magnetic activity cycle.